Georgia First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion-Staff Report; Staff Statement; Press Release; and Statement by the Executive Director for Georgia (IMF Staff Country Reports, 2005)
The staff report for the First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility on Georgia highlights economic developments and policies. Growth has remained robust and inflation subdued against the backdrop of steady remonetization. Rapid growth in fiscal revenue has permitted a faster-than-expected clearance of domestic arrears. Parliament is expected to vote shortly on a tax reform bill designed to streamline the tax code and encourage investment. Structural reforms will continue to be geared toward consolidating the fiscal position, deepening financial sector reforms